2020
DOI: 10.7241/ourd.20201.30
|View full text |Cite
|
Sign up to set email alerts
|

A vesicating dermatitis from a blister beetle, in the neck of Septuagenarian Saudi male

Abstract: A 72 years old Saudi male presented with an itchy and mildly painful skin lesion on the left side of the neck after being contacted before 2 days by a blister beetle while sleeping at night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In our study, the majority of patients were females presenting with cosmetic problems, which is consistent with other studies. 1,32 However, the effect of sex on morbidity has not been determined, as other studies have also reported a high morbidity rate in men. 33 The fact that women are more conscious of their appearance than men may explain the higher incidence in women in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the majority of patients were females presenting with cosmetic problems, which is consistent with other studies. 1,32 However, the effect of sex on morbidity has not been determined, as other studies have also reported a high morbidity rate in men. 33 The fact that women are more conscious of their appearance than men may explain the higher incidence in women in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…GCPRs are nested in the GCX of the cell membrane, which binds extracellular substances and transmits signals to an intracellular molecule called a G protein (guanine nucleotide-binding protein) [176]. GCX disruption affects the GPCRs downstream signaling pathways and the enzymes associated with these downstream pathways are the targets of drug development [177]. These are epigenetics in nature and could be temporary, occur during a lifetime, or heritable [178].…”
Section: Drug Discovery Paradigmsmentioning
confidence: 99%
“…Warts are common benign lesions caused by the human papillomavirus, which affect approximately 10% of the global population. 1 In high‐risk populations such as children or immunocompromised individuals, the prevalence may be as high as 20% percent. 1 Despite the expanding arsenal of wart therapies, recalcitrant verrucae are quite common not only in those with predisposing risk factors but also in many otherwise healthy persons.…”
Section: Introductionmentioning
confidence: 99%